Dasatinib and Prednisolone Induction Therapy for a Case of Philadelphia Chromosome-Positive Acute Lymphoblastic Leukemia with Dilated Cardiomyopathy Accompanied by Life-Threatening Ventricular Tachycardia - Mitsutaka Nishimoto; Hirohisa Nakamae; Kana Matsumoto; Kunihiko Morita; Yuki Koga; Dai Momose; Masayuki Hino (Case Reports in Hematology)
A 56-year-old man being treated for dilated cardiomyopathy presented with epigastralgia. He was diagnosed with ventricular tachycardia and Philadelphia chromosome-positive acute lymphoblastic leukemia. After treating incessant ventricular tachycardia, we commenced induction therapy for leukemia with dasatinib and prednisolone to minimize toxicity towards cardiomyocytes and the cardiac conduction system. Although dasatinib was temporarily withheld because of a recurrence of ventricular tachycardia, we rechallenged dasatinib while using bisoprolol and amiodarone and achieved a complete hematological response three weeks later. Although drug interactions between dasatinib and amiodarone were of concern, the blood concentration of each drug remained within the safe range after concomitant use, and there were no adverse cardiac effects such as QT prolongation after rechallenging dasatinib. Induction therapy with dasatinib and prednisolone may be an acceptable therapeutic option for Philadelphia chromosome-positive acute lymphoblastic leukemia with severe cardiac complications.